Истраживање потенцијала мрачног туризма у Керали: анализа и документација атракција - k t, sanoj k t (Turizam, 2025)
Tourism is linked to concepts like leisure, joy, and enjoyment. The growth of niche tourism is essential, as individuals are now placing a greater emphasis on alternative travel than on conventional mass tourism. Even while India has made significant headway in creating specialized tourism, one particular industry Dark Tourism has not yet been developed. Dark tourism has become incredibly popular in the twenty-first century all across the world. The growth of the notion of special interest tourism and changing tourist tastes and preferences have compelled tourism policymakers worldwide to include this segment in their mission and vision statements. Several war-torn, underdeveloped nations that struggled to draw tourists due to a lack of supportive infrastructure have begun to welcome travelers for dark tourism since it gives them a competitive edge. Kerala, a state located on the south western coast of India is a popular tourist destination in India known for its beautiful beaches, backwaters, and rich culture and history has many places to engage in dark tourism. This paper attempts to address the potential of dark tourism in Kerala.